Comparative Susceptibility Study Against Pathogens Using Fermented Cranberry Juice and Antibiotics - Mantzourani, Ioanna; Bontsidis, Christos A.; Plessas, Stavros; Alexopoulos, Athanasios; Theodoridou, Eirini; Tsigalou, Christina; Voidarou, Chrysa; Douganiotis, George; Kazakos, Stavros L.; Stavropoulou, Elisavet; Bezirtzoglou, Eugenia (Frontiers in Microbiology, 2019)
In the present study, unfermented and fermented cranberry juice with a recently isolated potentially probiotic Lactobacillus paracasei K5 cooperated with various antibiotics (tigecycline and vancomycin) was tested for its antimicrobial activity. The tested strains selected for this purpose were Enterococcus faecalis, Enterococcus faecium, Enterobacter cloacae and Staphylococcus aureus. The methods followed were the determination of zones inhibition, MIC (Minimum Inhibitory Concentration) and FICI (Fractional Inhibitory Concentration Index). In case of tigecycline and fermented juice application, Zones of Inhibition (ZOI) were larger in strains of Enterococcus faecium (65±4.8mm) compared to the respective ZOI with tigecycline and unfermented juice (no zone). Same outcome was obtained in the case of Enterobacter cloacae. Regarding cooperation of vancomycin with fermented juice the outcome obtained showed that ZOI were larger in strains of Enterococcus faecium (28±2.2mm) compared to the respective ZOI with vancomycin and unfermented juice ( 24±2.3mm). The lowest MIC values were recorded during application of tigecycline and fermented cornelian cherry juice against S.aureus strains, followed by Enterobacter cloacae strains. FICI reveals synergism between tigecycline and fermented juice in one strain of Enterococcus faecium(A2020),one strain among Enterococcus faecalis (A 1940) and in one strain of S.aureus (S 18) when vancomycin and fermented juice was applied against it. Among Enterobacter cloacae (E 1005 & E1007) strains, tigecycline and fermented juice exhibited synergism when used in combination. Results indicate that antibacterial activity of fermented juice with the potentially probiotic Lactobacillus paracasei K5 may be due to synergistic effects of some end fermentation products with the antibiotic agents examined.